The Complementary Relationship Between Echocardiography and Multi-Slice Spiral CT Coronary Angiography in the Diagnosis of Coronary Artery Thrombosis in Children With Kawasaki Disease - Xu, Yun-ming; Chu, Yan-qiu; Li, Xue-mei; Wang, Ce; Ma, Quan-mei; Yu, Xiao-na; Yu, Xian-yi; Chen, Rui; Xing, Yan-lin; Yu, Xue-xin; Sun, Le; Cui, Xiao-zhe; et al. (Frontiers in Pediatrics, 2021)
Aim: To compare the diagnostic values by using transthoracic echocardiography (ECHO) and multi-slice spiral CT coronary angiography (CTCA) for identifying coronary artery thrombosis in children with Kawasaki disease (KD). Methods: Total 97 KD children with coronary artery dilatation complication in our hospital from Jun 2012 to Dec 2020 were included in the study. CTCA and ECHO were performed after over one month of illness. Results: Coronory artery thrombosis was found in 14 out of 97 patients. Among of them, 10 were identified as positive in CTCA and 9 were identified as positive in ECHO, 5 were identified as positive in both CTCA and ECHO. Conclusion: Both CTCA and ECHO can be used for diagnosing coronary artery thrombosis. ECHO has advantage in low-density thrombus, and CTCA is better for the clot in distal coronary artery. They can complement each other.